2008
DOI: 10.1093/humrep/den476
|View full text |Cite
|
Sign up to set email alerts
|

Does low-dose aspirin improve pregnancy rate in IVF/ICSI? A randomized double-blind placebo controlled trial

Abstract: This randomized controlled trial could not show a significant difference in clinical pregnancy rate between the aspirin and the placebo group in a first or second IVF/ICSI cycle. Given the lack of evidence for a beneficial effect of low-dose aspirin, it appears that low-dose aspirin should not be prescribed routinely in IVF/ICSI treatment. ClinicalTrials.gov Identifier: NCT00644085.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…Given the influence of inflammation on implantation, low-dose aspirin (LDA), an antiinflammatory drug, may improve implantation through reduction of inflammation. Indeed, some small trials noted that LDA increased the clinical pregnancy rate among women undergoing in vitro fertilization, although results were mixed (15)(16)(17)(18)(19). Recently, the Effects of Aspirin in Gestation and Reproduction (EAGeR) trial reported that preconception LDA treatment increased the probability of becoming pregnant, but did not prevent pregnancy loss, among women who were attempting pregnancy without fertility treatments and had a history of 1 pregnancy loss in the previous 12 months (20).…”
Section: Introductionmentioning
confidence: 99%
“…Given the influence of inflammation on implantation, low-dose aspirin (LDA), an antiinflammatory drug, may improve implantation through reduction of inflammation. Indeed, some small trials noted that LDA increased the clinical pregnancy rate among women undergoing in vitro fertilization, although results were mixed (15)(16)(17)(18)(19). Recently, the Effects of Aspirin in Gestation and Reproduction (EAGeR) trial reported that preconception LDA treatment increased the probability of becoming pregnant, but did not prevent pregnancy loss, among women who were attempting pregnancy without fertility treatments and had a history of 1 pregnancy loss in the previous 12 months (20).…”
Section: Introductionmentioning
confidence: 99%
“…There is conflicting evidence about the potential risks of miscarriage in early pregnancy with preconception or early pregnancy use of aspirin. While two studies (Nielsen et al, 2001 andLi et al, 2003) reporting increased risk of miscarriage included women taking non-steroidal anti-inflammatory drugs including aspirin rather than only those taking specifically aspirin in the study group, another two studies (Coomarasamy et al, 2003;Dirckx et al, 2009) evaluating women taking aspirin alone reported similar miscarriage rates between the study and control groups. However, certain reports of an increased risk of early trimester miscarriage (Li et al, 2003) and on higher ectopic pregnancy rates (Urman et al, 2000) cause some concerns on periconception use of aspirin and there is need for further evaluation on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the effect of aspirin/heparin on the outcome of assisted reproduction treatment in women with a failed IVF cycle and, despite the heterogeneity of these studies with regard to selection of participants and interventions, the evidence supporting the use of these therapies is still inconsistent (Check et al, 1998;Dirckx et al, 2009;Duvan et al, 2006;Kutteh et al, 1997;Lambers et al, 2009;Moini et al, 2007). The primary aim of this study was to investigate data from a tertiary fertility unit to see if there is any evidence that using low-dose aspirin with or without heparin as adjuvants in IVF treatment in women with history of at least one unexplained implantation failure improves implantation, clinical pregnancy and live birth rates.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed mechanisms for RIF include embryo or endometrial factors, as well as decreased endometrial receptivity, which could be related to uterine anomalies, endometriosis, hydrosalpinx, and thrombophilia [4546]. Empirical therapy strategies with aspirin and heparin showed no benefit for cases of unexplained RIF [474849]. A randomized clinical trial showed that immunological treatment with IVIG did not improve the live-birth rate in cases of unexplained RIF [50].…”
Section: The Validity Of Ivig Therapy For Each Indicationmentioning
confidence: 99%